Contribution of traditional deep fermentation to volatile metabolites and odor characteristics of Wuyi rock tea - Jia, Xiaoli; Wang, Yuhua; Li, Qisong; Zhang, Qi; Zhang, Ying; Lin, Shaoxiong; Cheng, Pengyuan; Chen, Meihui; Du, Mengru; Ye, Jianghua; Wang, Haibin (Frontiers in Bioengineering and Biotechnology, 2023)
Fermentation is extremely important for the formation of the special flavor of Wuyi rock tea. This study focused on the effect of traditional deep fermentation technology on volatile metabolites and odor characteristics of Wuyi rock tea. The results showed that 17 characteristic compounds significantly changed during the first stage of the preliminary processing, namely fresh leaves, withering and fermentation. The key to the formation of floral aroma lied in dihydromyrcenol, and the woody aroma derived from six terpenoids, and their synthesis depended on dihydromyrcenol content. The fruity aroma was dominated by six esters, and the fruity aroma mainly came from (Z) -3-hexen-1-yl butyrate, (E) -3-hexen-1-yl butyrate and 5-Hexenyl butyrate. This study provided an important theoretical and practical basis for improving the preliminary processing of Wuyi rock tea.